Articuler les logiques intrinsèques du médiateur culturel et du jeune public en situation de visite muséale - Dounia Lahoual; Anne Bationo-Tillon; Françoise Decortis (Perspectives Interdisciplinaires sur le Travail et la Santé)
Based on observational data from a guided tour combined with a self-confrontation interview, we propose, in this article, to combine the viewpoints of the two actors who met in a museum visit. By comparing the guide’s and the young visitors’ point of views about the activity, we show the moments, throughout the tour, when these viewpoints both bumped into each other and converged and how they contributed to the encounter with a work of art. A systemic analysis of the activity allowed us to identify several criteria to consider so as to insure a successful museum visit. The final results help in the design and co-construction of cultural mediation devices adapted to both visitors and mediation professionals.